Parents' gesture adaptations to children with autism spectrum disorder. Issue 1 (7th January 2020) - YOSHIDA, Hanako; CIRINO, Paul; MIRE, Sarah S.; BURLING, Joseph M.; LEE, Sunbok
Abstract: The present study focused on parents' social cue use in relation to young children's attention. Participants were ten parent–child dyads; all children were 36 to 60 months old and were either typically developing (TD) or were diagnosed with autism spectrum disorder (ASD). Children wore a head-mounted camera that recorded the proximate child view while their parent played with them. The study compared the following between the TD and ASD groups: (a) frequency of parent's gesture use; (b) parents' monitoring of their child's face; and (c) how children looked at parents' gestures. Results from Bayesian estimation indicated that, compared to the TD group, parents of children with ASD produced more gestures, more closely monitored their children's faces, and provided more scaffolding for their children's visual experiences. Our findings suggest the importance of further investigating parents' visual and gestural scaffolding as a potential developmental mechanism for children's early learning, including for children with ASD.